Characterisation of ureteric obstructive lesions using single bolus CT urography: a single centre study - Varaprasadvarma, Pavankumar Suraparaju; Titare, Prashant; Rote Kaginalkar, Varsha (International Journal of Research in Medical Sciences, 2024)
Background: CT urography which has replaced IVP is an imaging procedure in which the contrast is injected and phases of CT scan are taken to study the entire urinary system. Advantages include the use of multiplanar reconstruction (MPR), reformatted images, maximum intensity projection (MIP) and three-dimensional (3D) reconstruction which gives valuable information. This study aimed to characterize ureteric abnormalities, site, nature and severity of obstruction in cases of begin and malignant obstructive uropathy using CT Urography. Methods: This is a tertiary hospital Government medical college, Aurangabad based ddescriptive Cross sectional observational study on 360 patients referred for CT urography with clinical signs and symptoms of urinary tract, having ureteric imaging abnormalities from November 2020 to December 2022. Siemens somatum 128 slice CT High Definition scanner was used. Results: Benign obstructive causes were more common in our study accounting for 80.7% cases. Among total of 74 malignant cases, 55 cases had obstructive involvement of urinary system with maximum of Ca cervix and ovary predominantly at VUJ. Benign causes were more common in mild hydronephrosis predominantly and malignant involvement of ureters were most commonly seen in severe hydronephrosis. Conclusions: This study highlights the severity and site of obstructive uropathy in benign and malignant causes. It implies application of delayed phase of CT urography (hybrid CT urography) on case to case basis to study ureteric involvements based on various pathologies.